(2S)-3-(1H-Indol-3-yl)-2-(4-methylbenzenesulfonamido)propionic acid monohydrate - Islam Ullah Khan; Muhammad Nadeem Arshad; Hafiz Mubashar-ur-Rehman; William T. A. Harrison; Muhammad Baqir Ali (Acta Crystallographica Section E, 2011)
In the title compound, C18H18N2O4S·H2O, the indole and toluene ring systems are oriented at a dihedral angle of 84.51 (9)°. In the crystal, the components are linked by N—H...O, O—H...O, C—H...O and N—H...π interactions. These include a short link from the α-C atom of the amino acid fragment.